A THEORETICAL MODEL FOR REVERSE WATER-LEVEL FLUCTUATIONS INDUCED BY TRANSIENT PERMEABILITY IN THRUST FAULT ZONES - Stanislavsky E.; Garven G. (My University, 2003)
A numerical model was applied to simulate the poroelastic response to changes in fault permeability as a result of earthquakes. The 'fault valve' model describes faults as impermeable barriers for fluids except immediately after earthquakes, when fault zones are damaged and transient pathways for fluids are created. In this case the fault is viewed as a discharging well, draining fluids from the surrounding rock. The reverse water-level effect is characterized by the increase of water level in adjacent aquifers and aquitards, resulting from withdrawing fluids through a well. Theoretical calculations suggest that the reverse water-level effect exists also in earthquake cycling and is in the same order of magnitude as the co-seismic hydraulic head change. A significant rise of the hydraulic head (>1 m) occurs within the country rock from both sides of the fault. The rise of the water level takes months to years to occur, and perhaps that is why it cannot be easily distinguished from seasonal hydrologic changes observed in the field. The reverse water-level effect also propagates away from the fault at a rate of hundreds of meters per year, depending on the permeability of the country rock. In deep formations where the permeability is low, the propagation takes years. The magnitude of the reverse water-level effect is greater when the fault efficiently drains fluids, when it is highly permeable and slow to reseal.